OPTIMALISASI TRANSFORMASI DIGITAL PAJAK DALAM MENDORONG UMKM KREATIF DI TORAJA UTARA - Srisetyawanie Bandaso; Wilma Dian Ardiyanti; Dedy Bulelenan (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to describe how digital tax transformation contributes to improving tax compliance and fostering the economic growth of creative MSMEs in North Toraja Regency. The digital transformation is implemented through online-based systems such as e-Registration, e-Filing, e-Bupot, and e-Faktur, which simplify the tax reporting process without requiring business owners to visit tax offices in person. Using a qualitative approach with in-depth interviews involving creative MSME actors and tax officers, the study finds that the digital system enhances the efficiency and transparency of tax administration. However, several challenges remain, including limited internet access, low digital literacy, and insufficient technical assistance. The findings indicate that digital transformation positively influences tax compliance, particularly among MSMEs that have participated in tax socialization and digital training programs. Improved tax compliance subsequently promotes economic growth through greater business legality, consumer trust, and access to financing. Therefore, digital tax transformation not only simplifies fiscal administration but also serves as a catalyst in building an inclusive and sustainable creative economic ecosystem in North Toraja. Keywords : Creative MSMEs; Digital Tax Transformation;Economic Growth; Tax Compliance.